PEMASARAN GLOBAL DI ERA KECERDASAN BUATAN : PELUANG DAN TANTANGAN UNTUK BRAND INTERNASIONAL - Triana Hasty Kusuma; Sari Wijayanti; Novita Yuliana; Rizka Fatkhin Nisa; Stevi Jimry Poluan (Universitas Dharmawangsa, 2025)
The advancement of Artificial Intelligence (AI) technology has significantly transformed global marketing strategies, particularly for international brands. This study aims to identify the opportunities and challenges faced by brands in integrating AI into their global marketing approaches. Using a qualitative method, data were collected through in-depth interviews and document analysis from various relevant sources. The findings reveal that AI offers substantial opportunities in service personalization, operational efficiency, and predictive insights into consumer behavior. However, several challenges remain, including technological infrastructure gaps, data privacy issues, and organizational resistance to digital transformation. Therefore, international brands must adopt adaptive, ethical, and sustainable strategies in implementing AI to effectively compete in the ever-evolving global market.